Pengaruh Media Baru Terhadap Partisipasi dan Keterlibatan Anak Muda Dalam Politik - Azis, Hasbullah (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
The new media is considered to have facilitated a new approach to political engagement and participation because it has a different quality from the previous media. New media has facilitated the production, mobilization, and exchange of political content mediated by various online media platforms. By conducting a literature review, this research refers to the tradition of media effects which cuts media effects into two dimensions. First, the effect of the media is very strong in shaping the behavior of its audience. Second, the effect takes place dynamically where many factors interact variously shaping influence. Based on the result of the review, this article found that new media has great potential not only to mobilize, but also to expand political engagement and participation among young people in addition to other factors such as the cognition process, economics, and the political system of government, which also have an influence on media use which led to the engagement and participation of youth in politics.